PENDIDIKAN AKHLAK DALAM KITAB BULUGHUL MARAM - Hirzulloh, Muhammad Faiq (PKBM DAARUL AHKAAM, 2024)
The world of education is currently facing many complicated issues. These include ethical issues that arise among teenagers, such as drug prevention and abuse (addiction). Ultimately, this becomes an unresolved social problem. Knowledge, training, management and a good environment are needed to shape and build good learner morals. Kitab Bulughul Maram, which contains material on morals, can be used to teach this so that students have a firm morality. Seeing and studying the formation of ethics in human relationships with God, self, and others is the purpose of this research. Literature study is the approach used to conduct statistical evaluation. However, the research method he used was descriptive qualitative.This evaluation shows that moral training resides within the relationship between man and God.It is mainly concerned with the abolition of communion and devotion to God. Toward oneself is a strong and compassionate painting.With others, especially, helping everyone, filial piety, giving alms, doing good, helping everyone, inviting kindness, inviting friendship, and stopping hurting everyone for more than three days. With others, especially: helping everyone, filial piety, giving alms, doing good, helping everyone, inviting kindness, inviting friendship.